MANAJEMEN PENGELOLAAN KELAS DALAM MENINGKATKAN MUTU PEMBELAJARAN PAI DI SMP ISLAM DARUL ULUM CONDONG GADING TAHUN PELAJARAN 2017-2018 - Tri Wisudaningsih, Endah; M. Huzin (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2019)
Abstract Teaching and learning processes held in several schools as a center for formal education are more intended to direct changes in themselves in a planned manner both in terms of cognitive, affective and psychomotor. The role of the teacher is very important in education. Good or bad education is influenced by how a teacher can manifest and apply his contribution to formal institutions to realize the intelligence of the nation and the ideals of the country, so that between teacher and education is an inseparable component. Therefore, In reality, in the field of Islamic Religious Education subjects today the quality is still vulnerable because it has not reached the desired target adequately, especially in public schools. In addition to this reality, there is an assumption that "In school life we ​​often see teachers who can be said to be unsuccessful in teaching. This failure is not only the teacher's failure to teach his task of mastering the subject matter when delivering it, but the teacher's ignorance in managing the class. One of the priority efforts to achieve this is to improve the quality of education. To improve the quality of education, all components of education also need to be improved. In addition, with the regional autonomy, a new decision in the education sector has emerged related to efforts to improve the quality of school education, namely School Based Management. In implementing SBM effectively and efficiently, teachers must be creative in improving classroom management appropriately so that learning takes place maximally, efficiently and effectively. One effort that can be used as a solution in the problem of PAI learning is the implementation of classroom management in PAI learning, especially in this Junior High School. This Darul Ulum Condong Islamic Junior High School is one of the institutions that strives to improve students' abilities in productive programs, adaptive programs and normative programs . Researchers conducted research at the Darul Ulum Condong Islamic Middle School because the researchers wanted to know about how PAI teachers at the Darul Ulum Condong Islamic Middle School manage their classes so that learning is in line with the expected goals, even though many students lack religious knowledge and lack of time allocation for learning. Keywords: Classroom Management, Education Quality, Islamic Religious Education